Eat this book : a carnivore's manifesto - Lestel, Dominique (Critical perspectives on animals., 2016)
If we want to improve the treatment of animals, Dominique Lestel argues, we must acknowledge our evolutionary impulse to eat them and we must expand our worldview to see how others consume meat ethically and sustainably. The position of vegans and vegetarians is unrealistic and exclusionary. Eat This Book calls at once for a renewed and vigorous defense of animal rights and a more open approach to meat eating that turns us into responsible carnivores. Lestel skillfully synthesizes Western philosophical views on the moral status of animals and holistic cosmologies that recognize human-animal reciprocity. He shows that the carnivore's position is more coherently ethical that vegetarianism, which isolates humans from the world by treating cruelty, violence, and conflicting interests as phenomena outside of life. Describing how meat eaters assume completely - which is to say, metabolically - their animal status, Lestel opens our eyes to the vital relation between carnivores and animals and carnivores' genuine appreciation of animals' life-sustaining flesh. He vehemently condemns factory farming and the terrible footprint of industrial meat eating. His goal is to recreate a kinship between humans and the animals that reminds us of what is means to be tied to the world.--COVER.